Dengue fever in the Federal District, and the challenges in the midst of the pandemic (Research, Society and Development, 2021)
Located in the Midwest Region, the Federal District is the smallest Brazilian federative unit and the only one that has no municipalities, being divided into 33 administrative regions, totaling an area of 5,779,999 km². The spread of the vector is wide between latitudes 35ºN and 35ªS, considered intertropical zones, in the case of Aedes aegypty. The present work aims to review factors determining reproduction, transmission and prevalence, as well as preventive measures and their efficiency together with public policies and participation of the population in helping to accurately map space-time in the administrative regions of the Federal District , potential risks to the population, status of virus serotypes, before and during the pandemic. The research was carried out in the Federal District with data referring to the period from 2015 to 2020. The data were obtained by the Department of Health Surveillance, Department of Health of the Federal District, epidemiological bulletins and current articles on Dengue and Dengue related to Covid-19 in scientific research platforms. The collaboration of society, health professionals and government representatives are the strength in combating covid-19, caused by the Sars-cov 2 virus, as well as Dengue with its serotypes. Thus, it is necessary to demand due importance to the two pathologies in a responsible and committed way, prioritizing public health in order to avoid a problematic lack of control by both Covid-19 and arboviruses, given the complexity of both, and their dependence on organizational processes. urban, social and governmental control.